The swaps index for consumer choice - Mia Lu; Nick Netzer (University of Zurich, Department of Economics, 2022)
We extend the swaps index of rationality, introduced by Apesteguia and Ballester (2015) for a finite set of alternatives, to the standard consumer choice setting with infinite commodity spaces. Applications include consumer demand from competitive budget sets and the state-space approach to choice under uncertainty. We are primarily interested in Apesteguia and Ballester's result that the swaps index recovers the decision-maker's true preference from choice data for a large class of boundedly rational behavioral models. We show that this result still holds in the consumer choice setting under a suitably defined monotonicity condition. This condition is satisfied for various models of interest but violated for others.
Keywords: D01; D11; D60; D90; 330; measures of rationality; revealed preference; behavioral welfare economics